1989
DOI: 10.1177/026309238900800204
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Assessment of the Vibration Discomfort Produced by Different Hand Held Machines

Abstract: A subjective method of paired comparisons was developed to compare the discomfort caused by the vibration from hand-held power tools with the predictions obtained using the procedures recommended by standards for the evaluation of human exposure to hand-transmitted vibration. Fiteen trained subjects were exposed in the laboratory to seven different vibration exposures produced by five hand-held tools (one of the tools was used in two positions) and an electrodynamic vibrator. The good agreement observed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Furthermore, the higher frequency limit has been questioned, since investigations have shown that vibrations with high frequencies, above 1 kHz, also have a detrimental effect on the operators (Lundström 1985a, Lundström & Lindmark 1982. Some evidence has also been reported which indicates that the impulsiveness of vibration is an additional factor in the development of vibration syndrome (Broyde et al 1989, Starck 1984b) and that the assessment should be based upon the sum of vibrations in all the three directions . NIOSH (1989) has also concluded that the use of the frequency-unweighted acceleration is a more appropriate means of assessing the health risk to exposed workers.…”
Section: The Risk Assessmentmentioning
confidence: 99%
“…Furthermore, the higher frequency limit has been questioned, since investigations have shown that vibrations with high frequencies, above 1 kHz, also have a detrimental effect on the operators (Lundström 1985a, Lundström & Lindmark 1982. Some evidence has also been reported which indicates that the impulsiveness of vibration is an additional factor in the development of vibration syndrome (Broyde et al 1989, Starck 1984b) and that the assessment should be based upon the sum of vibrations in all the three directions . NIOSH (1989) has also concluded that the use of the frequency-unweighted acceleration is a more appropriate means of assessing the health risk to exposed workers.…”
Section: The Risk Assessmentmentioning
confidence: 99%
“…Subsequently, in order to determine the effect of the vibrations on the human body the rms intensity in each band must be multiplicated by a proper weighting factor. It is in fact well known that human response to the hand-transmitted vibration varies enormously with frequency, and in particular, it is high at low frequency and greatly decreases with frequency (Reynolds et al, 1977;Broyde et al, 1989;Giacomin et al, 2004;Morioka and Griffin, 2006). ISO 5349 standard, in particular, recommends a weighting curve which shows a peak value for the weighting factor close to 1, in the range between 8 and 16 Hz, and a rapidly decreasing curve reaching values below 0.1 for frequencies above 150 Hz.…”
Section: Discussionmentioning
confidence: 99%